Mechanisms, clinical features and risk factors for stroke in the posterior cerebral artery infarcts - Şenay Aydın; Zehra Işıl Satılmış Borucu; Nevin Pazarcı; Dilek Necioğlu Örken; Hulki Forta (Türk Nöroloji Dergisi, 2015)
OBJECTIVE: The objective of our study is to investigate the association between the infarcts in the cortical and deep posterior cerebral artery perfusion area and the mechanisms of stroke, clinical features and risk factors. METHODS: For this purpose, 57 patients included in this study who suffered strokes first time and have infarcts in the posterior cerebral artery perfusion area and admitted to our Neurology Clinics between January 2002 and August 2007. Subjects were divided in two groups as cortical branch infarct group and deep (thalamus) + cortical branch group. Patients were evaluated in four etiologic clusters; 1.Occlusion in the posterior cerebral artery or its branches. 2. Occlusion proximal to the posterior cerebral artery. 3. Cardio-embolic reasons. 4. Cryptogenic embolism group. All patients had cranial CT, MRI, neck Doppler USG, MRA or DSA, trans-esophageal or trans-thoracic echocardiography, hematologic and vasculytic investigations. Risk factors in all patients were recorded. RESULTS: Thirty-five (61%) patients had cortical branch infarct, 22 patients (39%) had infarcts in the cortical and deep PCA perfusion area. The cardio-embolism (n: 27; 47%) was the most frequently observed etiologic factor in both groups. This is followed by intrinsic PCA disease (n: 12; 21%), proximal artery disease (n: 10; 17%), cryptogenic embolism (n: 8, 15%), respectively. Headache was observed in 52% of the patients at the beginning of stroke. Seventy-eight of the patients had visual disturbances, 54% had motor symptoms, 24% had sensorial symptoms. CONCLUSION: It is concluded that cardiogenic embolism and intrinsic PCA disease are more frequent etiologic factors in infarcts observed in the cortical and deep posterior cerebral artery perfusion area. There was no statistical difference in etiology and risk factors between the patients who had PCA cortical branch infarct group and deep (thalamus) + cortical branch group.